SVIATOSLAV KARAVANSKY IN THE UKRAINIAN DISSIDENT MOVEMENT (1960S – 1970S) (Південний архів (історичні науки), 2025)
The purpose of the article is a comprehensive and complex analysis of Svyatoslav Karavansky’s participation in the Ukrainian dissident movement from the early 1960s to the late 1970s. The methodological basis of the article was the principles of objectivity, historicism, comprehensiveness, continuity, as well as a complex of special-historical and general scientific methods. The work used methods of analysis and synthesis, retrospective, problem-chronological, and the method of comparison and comparison of information from various sources. Results and conclusions. The life path of S. Karavansky in the 1960s–1970s is a striking example of unwavering loyalty to the ideals of national revival, civic dignity, and intellectual resistance to Soviet totalitarianism. His activities within the Ukrainian dissident movement went far beyond personal protest – it took on the character of a long and consistent struggle, combining cultural and educational, journalistic, linguistic and human rights aspects. Sviatoslav Karavansky spoke not only against political repressions, but also against the deeper processes of Russification and the destruction of national identity. His public addresses, protest letters, literary and scientific activities, including the creation of the “Dictionary of Ukrainian Rhymes” and the publication of articles, became important acts of resistance, aimed at both a domestic audience and the international community. S. Karavansky’s imprisonment did not break his spirit, but only deepened his convictions. His activity in the camps, participation in the creation of the “Code of Honor of a Political Prisoner”, hunger strike, and joining the Ukrainian Helsinki Group testify to his transition from individual to collective, structured resistance. S. Karavansky’s experience demonstrates that Ukrainian dissidence was not a homogeneous phenomenon, but had within itself different strategies and approaches to the struggle. At the same time, S. Karavansky personified the most resolute, active line of resistance, which combined personal sacrifice, intellectual work and strategic vision. His contribution to the preservation of Ukrainian national identity, human rights struggle and intellectual heritage is undoubtedly significant and deserves deep scientific understanding and due respect.
Keywords: Sviatoslav Karavansky, Ukrainian dissident movement, Ukrainian Helsinki Group (UHG), political imprisonment, Russification, Committee for State Security (KGB), Soviet regime